Biokonversi Serat Buah Sawit Menjadi Bioetanol Dengan Variabel Konsentrasi Saccharomyces Cerevisiae - Masroah Tuljannah; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Indonesia was the largest producer and exporter of palm oil in the world. As the plantation area expands, the increasing number of palm oil process industries results in large amounts of waste product. The biggest waste was of palm fruit fiber (fiber cake). It was known that 1 ton of fresh fruit bunches (FFB) of palm oil will produced 13% or 130 kg of fiber cake. By look at the potential that can be generated from the fruit fiber of palm oil (fiber cake) coming from the CPO process industry has a value that to use as the main ingredients in the making of alternative bioethanol fuel. The purposes of this study were to synthesize bioethanol from the raw material of palm fruit fibers, to determine the influence of the amount of Saccharomyces cerevisiae weight on bioethanol, and to determine the optimum time of bioethanol production from the raw material of palm fruit fibers by separation hydrolysis and fermentation (SHF) method. The stages of this study were delignification used KOH solution obtained from the extract of Palm Empty Cluster Ash, then the purification process using 3% H2O2 solution. Then the hydrolysis process using 2 M H2SO4 for 3 hours at 100°C. The last process was fermentation. In the fermentation process, variations of Saccharomyces cerevisiae concentration were 4, 6, 8 and 10 gr/L and fermentation time were 24, 48, 72, 96, and 120 hours. In acid hydrolysis, a maximum sugar concentration of 131 gr/L was produced. The research results show that the best Saccharomyces cerevisiae concentration was 4 gr/L at the best fermentation time of 96 hours with the obtained bioethanol content of 7% or 55.25 g/L.Keywords: bioethanol, fermentation, hydrolysis, palm fruit fiber, Saccharomyces cerevisiae